IMPLEMENTASI REWARD DAN PUNISHMENT DALAM SISTEM PENGELOLAAN PEMBELAJARAN DI PONDOK PESANTREN AZ-ZIKRA BOGOR - Muchammad Ibnu Muzakir; Aditya Soleha Putri (CV. ALIM'SPUBLISHING, 2024)
This study aims to develop a better reward and punishment system in the learning process at the Az-Zikra Islamic Boarding School, Bogor. This study used a qualitative method with descriptive data collection. The aim is to increase discipline, reduce bullying, increase learning motivation, and provide rewards to students. Achievement stars per semester, awards from the homeroom teacher, praise, and prizes as a form of reward. The form of punishment implemented at the Az-Zikra Islamic Boarding School in Bogor for students is in the form of warnings and advice, memorizing lessons and the Sunnah Prayers of the Prophet, writing astaghfirullah as specified, calling parents, notes on report cards and black lists for the heaviest offenders.